The in-utero experience of piglets born from sows with lameness shapes their life trajectory - Marisol Parada Sarmiento; Thiago Bernardino; Patricia Tatemoto; Gina Polo; Adroaldo José Zanella (Scientific Reports, 2021)
Abstract Experiences during gestation can alter the mother’s behavior and physiology, thereby potentially affecting the behavioral and physiological development of the offspring. In livestock, one common challenge for pregnant animals is lameness: a multifactorial condition that causes pain, stress, resulting in poor welfare outcomes. Since maternal pain can affect offspring development, we aimed to quantify the behavioral response in 142 piglets born from sows with different degrees of lameness during pregnancy. Gait scores of 22 pregnant group-housed sows were assessed six times at 2-week intervals. Lameness scores varied from 0 (no lameness) to 5 (most severe lameness score). Saliva samples and behavior were assessed in the sows throughout pregnancy. Sows were moved to individual farrowing pens and placental tissue was collected for glucocorticoid assessment. At 28 days of age, piglets were weaned, weighed, and regrouped by body size and sex. Skin lesions were counted for each piglet on days 28, 29, and 30 after birth. During open field and novel object tests on day 30, the vocalization and activity levels were evaluated. Piglet data were grouped by the lameness score of the sows as G1 (without lameness), G2 (moderate lameness), and G3 (severe lameness). Data analysis included ANOVA or Kruskal–Wallis tests and pairwise comparisons which were performed using Tukey and Kramer (Nemenyi) test with Tukey-Dist approximation for independent samples. G2 piglets were heavier than G3 at weaning. G1 piglets had fewer skin lesions at days 28 and 29 than G2 piglets. Moreover, G1 piglets vocalized more than G2 when they were subjected to the combined open field and novel object test. We did not identify differences among sows showing different lameness scores in the concentration of placental or salivary glucocorticoids. Lameness in pregnant sows altered the offspring’s weight gain, number of skin lesions and vocalizations, together showing evidence that lameness in sows affect offspring performance and behavior.